Neonatal Jaundice and Breast Feeding: A Narrative Review: Penyakit kuning pada bayi baru lahir dan pemberian ASI: Sebuah Tinjauan Naratif - Awad, Kadhim Jawad (Universitas Muhammadiyah Sidoarjo, 2024)
A significant proportion of both term and preterm neonates experience neonatal jaundice. Jaundice is the most common cause of readmission to the hospital in otherwise healthy-term infants. Serum bilirubin levels rise due to red blood cell lysis, which is the main cause of jaundice. The blood carries bilirubin as